The Relationship Of Maternal Knowledge And Compliance With Giving Vitamin A Capsules To Toddlers At Posyandu Delima, Binuang Public Health Center, Serang Regency, 2023 - Afriyanti, Lisa; Rismayanti, Tetin (CV. Inara, 2024)
Background The WHO has classified vitamin A deficiency as a public health problem affecting approximately one-third of children aged 6 to 59 months in 2013. According to the data from the Health Office of Banten Province, the administration of vitamin A capsules to toddlers aged 6-59 months is 81.3%. In a preliminary study conducted at the Delima Posyandu of Binuang Public Health Center, there were 220 toddlers. The interview results from 15 mothers with toddlers revealed that 6 mothers (40%) were compliant in giving vitamin A capsules to their children, while 9 mother’s (60%) were not compliant. This non-compliance is attributed to the mothers' lack of knowledge regarding the benefits of administering vitamin A for the health of their toddlers. Research Objective: The purpose of this research is to determine the relationship between maternal knowledge and compliance with giving vitamin A capsules to toddlers at Posyandu Delima of Binuang Public Health Center Serang Regency in 2023. Research Methods: This study is a quantitative research with a cross-sectional design. The population comprises all mothers with toddlers who visit the Posyandu Delima at Binuang Public Health Center, Serang Regency. The sample size for this research was determined using the Slovin formula, resulting in a total of 69 individuals. Research Results: The results of this study indicate a significant relationship between maternal knowledge and compliance with giving vitamin A capsules to toddlers, with a regression coefficient value of 76.5%, using the binary logistic regression model equation = -4,096+0,765x. Conclusions and Suggestions: There is a significant relationship between maternal knowledge and compliance with giving vitamin A capsules to toddlers at Posyandu Delima, Binuang Public Health Center Serang Regency. It is hoped that mothers who have toddlers will always pay attention to their children's health by eating foods that contain vitamin A and consuming vitamin A capsules according to schedule to meet their vitamin A needs.